2023
DOI: 10.1021/acs.iecr.3c00710
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design of Aqueous Two-Phase Systems for Biomolecule Partitioning

Abstract: Aqueous two-phase systems (ATPS) have exhibited superior performance in many biotechnological applications. To promote the implementation of these powerful platforms by industry in the downstream processing, an optimal design method is developed to tailor high-performance ATPS for partitioning biomolecules in this work. In this design method, two machine learning (ML) models that combine the artificial neural network (ANN) algorithm and group contribution (GC) method are respectively employed to predict the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…ML models have also been intensively used for development of membranes for UF 136,137 and APTS. 138–140…”
Section: Emergence Of Intelligent Biomanufacturing Processesmentioning
confidence: 99%
“…ML models have also been intensively used for development of membranes for UF 136,137 and APTS. 138–140…”
Section: Emergence Of Intelligent Biomanufacturing Processesmentioning
confidence: 99%
“…There is a direct correlation between the partitioning of biomolecules, which is quantified by the partition coefficient ( K ), and their physicochemical properties. These properties include isoelectric points, sizes, surface hydrophobicity, polymer molecular weight, polymer/salt concentrations, pH, and temperature. ,, The separations’ selectivity in ATPS has been enhanced under various conditions, which are problematically associated with the need to make structural changes in ATPSs or to modify biomolecules. , It is therefore becoming more necessary to find techniques that do not require the reformulation of system structures or biomolecules. By creating a mechanism that facilitates the transfer of the biomolecule between the two phases, biomolecules partitioning enhances in ATPS. , Nanoparticles fulfill this demand and improve biomolecule partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, machine learning (ML) algorithms such as artificial neural networks (ANNs) and support vector machine (SVM) have been employed to develop nonlinear GC models for predicting CO 2 solubility in ionic liquids, toxicity of ionic liquids, and physical properties of IL–H 2 O mixtures such as viscosity and surface tension . Additionally, hybrid modeling methods that combine GC methods and ANN algorithms have been introduced to model the phase equilibrium behavior of aqueous two-phase systems (ATPSs). , Recent works have also demonstrated the seamless integration of ANN-based GC models with computer-aided design methods for the optimal design of solvent and aqueous biphasic systems. Inspired by these successful applications, this study aims to combine the GC method with three popular ML algorithms, namely, ANN, XGBoost, and LightGBM, to build models for predicting the density and viscosity of IL–os–water mixtures. In our previous work, we studied the density, viscosity, and other properties of the IL–IL binary hybrid system and concluded that ANN and GC have a good combination .…”
Section: Introductionmentioning
confidence: 99%